2003
DOI: 10.1051/0004-6361:20030500
|View full text |Cite
|
Sign up to set email alerts
|

Multiband photometric re-classification of ROTSE-IδScuti type stars

Abstract: Abstract. We present multi-passband CCD photometry of 20 ROTSE-I δ Scuti type pulsating stars and 1 RR Lyrae star to reclassify their variable types using the comparison of amplitudes between V and I passbands. For the re-classification, we used a criterion that pulsating stars have larger amplitude differences between passbands than eclipsing binaries because brightness changes of pulsating stars are mainly due to the temperature variations. As a result, only six stars were re-confirmed as δ Scuti variables a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Secondly, we combined the newly determined times of maximum light with those provided by earlier studies (Eggen 1955;Broglia & Masani 1957;Spinrad 1959;Broglia 1961;Heiser & Hardie 1964;Fitch et al 1966;Gieren et al 1974;Langford 1976;Szeidl & Mahdy 1981;Joner & McNamara 1983;Jiang 1985;Peniche et al 1985;Hamdy et al 1986;Kim & Joner 1994;Agerer et al 1999;Agerer & Hubscher 2000Derekas et al 2003;Jin et al 2003;Hubscher 2005;Hubscher et al 2006;Klingenberg et al 2006;Zhou 2006;Ward et al 2008).…”
Section: Times Of Maximum Light and O − C Diagramunclassified
“…Secondly, we combined the newly determined times of maximum light with those provided by earlier studies (Eggen 1955;Broglia & Masani 1957;Spinrad 1959;Broglia 1961;Heiser & Hardie 1964;Fitch et al 1966;Gieren et al 1974;Langford 1976;Szeidl & Mahdy 1981;Joner & McNamara 1983;Jiang 1985;Peniche et al 1985;Hamdy et al 1986;Kim & Joner 1994;Agerer et al 1999;Agerer & Hubscher 2000Derekas et al 2003;Jin et al 2003;Hubscher 2005;Hubscher et al 2006;Klingenberg et al 2006;Zhou 2006;Ward et al 2008).…”
Section: Times Of Maximum Light and O − C Diagramunclassified
“…V2367 Cyg (KIC 9408694) was discovered in a ROTSE survey (Akerlof et al 2000) and confirmed as a HADS star by Jin et al (2003) and Pigulski et al (2009). The star was included in the Kepler commissioning run (Quarter 0 = Q0) and data were obtained for a duration of 9.73 d with continuous short‐cadence (SC) 1‐min exposures.…”
Section: Introductionmentioning
confidence: 97%
“…Thus, it is very difficult to identify the accurate type of variable stars based only on their single filter light curves. Hence at least two filters should be employed to see the change of the amplitude at different wavelength bands for accurate classification (Jin et al 2003(Jin et al , 2004.…”
Section: Detection and Classification Of Vari-able Starsmentioning
confidence: 99%